Large‐Size Growth of Ultrathin SnS2 Nanosheets and High Performance for Phototransistors. (13th April 2016) - Zhou, Xing; Zhang, Qi; Gan, Lin; Li, Huiqiao; Zhai, Tianyou
Abstract : 2D SnS2 nanosheets have been attracting intensive attention as one potential candidate for the modern electronic and/or optoelectronic fields. However, the controllable large‐size growth of ultrathin SnS2 nanosheets still remains a great challenge and the photodetectors based on SnS2 nanosheets suffer from low responsivity, thus hindering their further applications so far. Herein, an improved chemical vapor deposition route is provided to synthesize large‐size SnS2 nanosheets, the side length of which can surpass 150 μm. Then, ultrathin SnS2 nanosheet‐based phototransistors are fabricated, which achieve high photoresponsivities up to 261 A W −1 (with a fast rising time of 20 ms and a falling time of 16 ms) in air and 722 A W −1 in vacuum, respectively. Furthermore, the effects of back‐gate voltage and air adsorbates on the optoelectronic properties of the SnS2 nanosheet have been systematically investigated. In addition, a high‐performance flexible photodetector based on SnS2 nanosheet is also fabricated with a high responsivity of 34.6 A W −1 . Abstract : Large‐size ultrathin SnS2 nanosheets are synthesized via chemical vapor method with the side length up to 150 μm. The thickness of the SnS2 nanosheets can be found to be as thin as 10 nm. Phototransistors based on ultrathin SnS2 nanosheets exhibit a high responsivity, fast response rates, and a high detectivity.